MODERN TRENDS OF ENDOSCOPIC AND LABORATORY DIAGNOSTICS IN TREATMENT OF EARLY CANCER OF STOMACH - T. V. Bochkova; D. R. Mukhamadeeva (Креативная хирургия и онкология, 2017)
This article describes data reviews of the modern endoscopic and laboratory techniques which used in the detection of early forms of gastric cancer. Through advanced modern electronics, their high resolving power allow to detect pathological changes at an early stage of the disease, identify the mechanisms of their development for the future treatment and prevention.